DRIS Analysis of Nutrient Balance for High–Yielding Oil Palm Plantations in Peatlands - Imam Khoiri; Radian Radian; Tatang Abdurrahman (Institut Pertanian Bogor, 2025)
This study was conducted using an exploratory survey method to collect annual production data and analyze oil palm leaf samples from peatlands in several private oil palm plantations in West Kalimantan Province. The data obtained were analyzed using the Diagnosis Recommendation Integrated System (DRIS). The results showed that to achieve optimal production of 23.81–30.33 tons ha -1 year -1, the optimal nutrient ranges in the oil palm leaf tissue on peatland were N 2.20–3.03%; P 0.14–0.18%; K 0.52–1.03%; Mg 0.16–0.30%; Ca 0.31–0.65%; B 7.05–18.06 ppm; Zn 2.44–14.26 ppm; Cu 2.76–6.37 ppm; Mn 18.36–315.28 ppm; and Fe 38.90–92.40 ppm. The nutrient balance ratios in the oil palm leaves on peatland showed optimal ratios for N/P 14.72–19.11; N/K 1.88–5.42; N/Mg 8.25–15.75; N/Ca 3.89–7.77; K/P 3.51–6.46; Mg/P 1.08–1.85; Ca/P 1.94–4.24; K/Ca 1.07–2.31; K/Mg 2.33–4.63; Ca/Mg 1.54–2.69; B/N 2.70–7.05; B/Fe 47.16–116.26; B/K 11.93–32.65; B/Ca 18.73–34.48; and B/Mg 32.54–80.43. Oil palm plants cultivated on peatlands with high production groups (>25 tons ha -1 year -1) had average nutrient indices of N (-1.5), P (1.6), K (0.9), Ca (0.2), Mg (0.0), and B (-1.4), with nutrient requirements in the order of N > B > Mg > Ca > K > P. In contrast, plants in the low–production groups (<25 tons ha -1 year -1) had average nutrient indices of N (-8.3), P (-3.9), K (1.1), Ca (6.8), Mg (0.7), and B (2.9), with nutrient requirements in the order of N > P > Mg > K > B > Ca. Keywords: nutrient balance, oil palm, peatland